Operational Scenario Analysis Method for Civil Aircraft Based on Requirement Capture. Issue 1 (March 2021) - Yuwei, He; Yuchen, Sun; Xinai, Zhang; Ximei, Dai; Dongsheng, Chen
Abstract: Scenario analysis is an accepted method in civil aircraft requirements capture and validation.This paper introduces the operation scenario analysis method for requirement capture, including stakeholder identification, interaction activity analysis, design requirement capture, etc.Based on SysML language, the modeling and analysis of operation scenarios were carried out.Taking the push/tow scenario of civil aircraft as an example, the structure diagram, use case diagram, activity diagram and requirement diagram are formed by modeling. The design requirements in this scenario are captured through the interaction analysis between the different stakeholders and the aircraft.